Quantum information course for the undergraduate students of cyber security - Wei CHEN; Zhenqiang YIN; Zhengfu HAN; Nenghai YU (网络与信息安全学报)
Quantum information is a new discipline with the intersection of quantum physics and information technology,which has developed rapidly recently and has been on the road of industrialization.In contrast,the severe shortage of the practitioners,who can understand quantum information technology in depth,have become bottlenecks restricting the development of this technology.The lack of talent stems is from the lack of education,especially for the undergraduate students of engineering.Benefitting from the vigorous growth of quantum information in China,the fundamental of infiltrating the quantum information course in the undergraduate education of engineering can be performed,and some positive effects have been achieved.The course has carried out the teaching reforms,and practices in terms of teaching objectives,curriculum structure,practical methods,which have gained good teaching results.These teaching experiences and ideas provide a valuable reference for quantum information education in the cyberspace security discipline.